Pengaruh stres kerja dan lingkungan kerja terhadap produktivitas karyawan bagian sewing pada PT. Seyang Indonesia - Fitriah Indah Sari; Jaka Slameta; Rika Nurhidayah (Universitas Tangerang Raya, 2023)
This study aims to determine the effect of work stress and work environment on the work productivity of sewing employees at PT Seyang Indonesia. The research method was carried out with quantitative methods and the analysis method used was multiple linear regression analysis. The population in this study were 200 employees of PT Seyang Indonesia. The sample used in this study was using probability sampling technique with simple random sampling technique. The data collection procedure in this study was to use a questionnaire using a Likert scale and SPSS 25 programming: (1) there is an effect of work stress on employee productivity (tcount = 17.808 > ttable = 1.978), (2) there is an effect of work environment on employee productivity (tcount 16.671 > ttable = 1.978), and (3) there is an effect of work stress and work environment on employee productivity (Fcount = 2611.588 > Ftable = 3.07). So it shows that work stress and the work environment at PT Seyang Indonesia partially and simultaneously have a relationship that has a positive and significant effect on work productivity.